Complexity and geographical economics : topics and tools - Commendatore, Pasquale; Kayam, Saime Suna; Kubin, Ingrid (Cham : Springer, 2015)
The uneven geographical distribution of economic activities is a huge challenge worldwide and also for the European Union. In Krugmanℓ́ℓs New Economic Geography economic systems have a simple spatial structure. This book shows that more sophisticated models should visualise the EU as an evolving trade network with a specific topology and different aggregation levels. At the highest level, economic geography models give a bird eyeℓ́ℓs view of spatial dynamics. At a medium level, institutions shape the economy and the structure of (financial and labour) markets. At the lowest level, individual decisions interact with the economic, social and institutional environment; the focus is on firmsℓ́ℓ decision on location and innovation. Such multilevel models exhibit complex dynamic patterns ℓ́ℓ path dependence, cumulative causation, hysteresis ℓ́ℓ on a network structure; and specific analytic tools are necessary for studying strategic interaction, heterogeneity and nonlinearities.
Introduction -- Part A. Economic Geography Modelling -- Part B. Institutions and Markets -- Part C. Industrial Interactions.
Online resource; title from PDF title page (SpringerLink, viewed February 26, 2015).
Includes bibliographical references.
Keywords: Economic geography -- Econometric models; Economic geography -- Mathematical models; BUSINESS & ECONOMICS -- Economics -- General; BUSINESS & ECONOMICS -- Reference; Economic geography -- Econometric models; Economic geography -- Mathematical models; Electronic books